PENDIDIKAN ISLAM KONTEMPORER ANALISIS PEMIKIRAN AZYUMARDI AZRA DALAM MODERASI ISLAM DI INDONESIA - Bat’sa Khoiro; Ali Ahmad Yenuri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
Azyumardi Azra was a Muslim scholar born in Lubuk Alung, West Sumatra, on March 4, 1955. He was born to Azikar and Ramlah and was the third of six siblings. He was also a productive writer, producing not only books but also articles published in national and international journals. Many of his writings focus on history and contemporary educational issues relevant to the present time. His brilliant ideas are often used as solutions to various problems in Indonesia. One of his greatest achievements was transforming IAIN Syarif Hidayatullah into UIN Syarif Hidayatullah in 2002, during his tenure as the tenth rector of UIN Syarif Hidayatullah. In this study, the research problem formulated by the researcher is: How is the concept of contemporary Islamic education analyzed through the thoughts of Azyumardi Azra?This research is a library study, as data were collected using documentation sourced from written works in the literature. The descriptive-hermeneutic approach, using double-movement hermeneutics, is a research method focused on describing and interpreting the meaning of the phenomena studied. In this context, the researcher attempts to gain a deeper understanding of the texts and intellectual context of Azyumardi Azra’s thoughts and their application within the framework of Islamic education in Indonesia. The results of the study show that Azyumardi Azra’s ideas regarding the concept of contemporary Islamic education provide significant benefits to the Muslim community. Important aspects of his thinking include the democratization of education, educational modernization, educational quality, the integration of science and religion, and character education. The relevance of Azra’s contemporary Islamic education to religious moderation lies in its efforts to shape Muslim individuals who understand religious teachings comprehensively, are tolerant of differences, and are capable of interacting positively within a pluralistic society.